All-solid-state light super capacitor based on carbon-rich carbon nitride conjugated polymer and preparation method of all-solid-state light super capacitor
By using a combination of carbon-rich carbon nitride conjugated polymer and titanium dioxide nanocrystalline mesoporous film in the optical supercapacitor, the problem of low photogenerated charge storage capacity and safety of liquid electrolyte is solved, and high efficiency is achieved , safe photogenerated charge storage.
Patent Information
- Application Number
- CN202411538532.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing optical supercapacitors are not high in photogenerated charge storage capacity, and the use of liquid electrolytes has problems with safety and stability.
Using an all-solid-state optical supercapacitor based on carbon-rich carbon nitride conjugated polymer, the titanium dioxide nanocrystalline mesoporous film is sintered on the conductive surface of the conductive glass and coated with carbon-rich carbon nitride conjugated polymer on its surface, thus forming a Symmetric capacitor structure containing electrolyte.
A high level of photogenerated charge storage capacity is achieved, the safety and stability problems brought about by electrolytes are avoided, and the device structure is simplified, improving long-term stability and safety.
Smart Images

Figure CN119400603A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar photovoltaic conversion and energy storage, and relates to an all-solid-state optical supercapacitor based on a carbon-rich carbon nitride conjugated polymer and a preparation method thereof. Background Art
[0002] Photosupercapacitors are devices that induce photogenerated charges under light and store them; when needed, they release the photogenerated charges to form current. The existing technology has the following problems:
[0003] (1) The photogenerated charge storage capacity is not high. Existing photosupercapacitors are mainly composed of a photovoltaic electrode and an energy storage electrode sharing a counter electrode. Photovoltaic materials absorb light to generate photogenerated charges, which are then input into the energy storage electrode material for charge storage. This mechanism requires that the voltage window and current size between the photovoltaic electrode and the energy storage electrode be very well matched, otherwise a large internal electron loss will occur, reducing the efficiency of photoelectric conversion and charge storage, and seriously affecting the photogenerated charge storage capacity.
[0004] (2) Problems caused by the use of electrolytes. Existing photosupercapacitors all use electrolytes to promote the separation of photogenerated charges or to stably store charges. Since supercapacitors use huge surfaces for charge storage, and the active surfaces come from the nanopores or mesoporous structures of the electrode materials, only liquid electrolytes can achieve a good wetting effect. However, the organic solvents in liquid electrolytes are prone to combustion or explosion due to overheating, causing safety issues. If solid electrolytes are used, the surface activity is greatly affected due to the poor contact between the electrolyte and the electrode material due to the small gaps, resulting in a serious decrease in storage capacity. At the same time, since photosupercapacitors need to be exposed to light for a long time, liquid electrolytes are easy to volatilize, which will increase the difficulty of device packaging and reduce performance stability. Summary of the invention
[0005] In view of this, the object of the present invention is to provide an all-solid-state optical supercapacitor based on carbon-rich carbon nitride conjugated polymer and a preparation method thereof, so as to prepare an all-solid-state optical supercapacitor without using an electrolyte with high photogenerated charge storage capacity.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A fully solid-state optical supercapacitor based on a carbon-rich carbon nitride conjugated polymer comprises a first conductive glass and a second conductive glass; a first titanium dioxide nanocrystalline mesoporous film is provided on the conductive surface of the first conductive glass; a second titanium dioxide nanocrystalline mesoporous film is provided on the conductive surface of the second conductive glass; a carbon-rich carbon nitride conjugated polymer is provided between the first titanium dioxide nanocrystalline mesoporous film and the second titanium dioxide nanocrystalline mesoporous film; the first titanium dioxide nanocrystalline mesoporous film, the second titanium dioxide nanocrystalline mesoporous film and the outer sides of the carbon-rich carbon nitride conjugated polymer are sealed by an insulating sealant.
[0008] On the other hand, the present invention provides a method for preparing an all-solid-state optical supercapacitor based on a carbon-rich carbon nitride conjugated polymer, comprising the following steps:
[0009] S1: Preparation of carbon nitride-rich conjugated polymers;
[0010] S2: Sintering titanium dioxide nanocrystalline mesoporous thin films on the conductive surfaces of two pieces of conductive glass to obtain a conductive glass-TiO2 nanocrystalline mesoporous thin film composite electrode;
[0011] S3: Uniformly coating the carbon nitride-rich conjugated polymer on the surface of the titanium dioxide nanocrystalline mesoporous film of the two composite electrodes;
[0012] S4: Two composite electrodes coated with carbon-rich carbon nitride conjugated polymers are bonded together using an insulating sealant to obtain an all-solid-state optical supercapacitor.
[0013] Further, the preparation steps of the carbon-rich carbon nitride conjugated polymer are as follows:
[0014] S11: dicyandiamide, citric acid, and deionized water are mixed in a mass ratio of 1:1.9:60 to obtain a reactant;
[0015] S12: introducing the reactants into a hydrothermal reactor and keeping the temperature at 200° C. for 3 hours to perform a hydrothermal reaction to obtain a precursor;
[0016] S13: sealing and storing the precursor at room temperature in an ammonia atmosphere for 3 to 14 months for aging reaction to obtain an aqueous solution of a carbon nitride-rich carbon conjugated polymer;
[0017] S14: freeze-drying the aqueous solution of the carbon-rich carbon nitride conjugated polymer at -80°C and a vacuum degree below 30 Pa to obtain a carbon-rich carbon nitride conjugated polymer solid material.
[0018] Furthermore, the titanium dioxide nanocrystalline film has an area of 3 cm×3 cm to 9 cm×9 cm and a thickness of 10 to 30 μm.
[0019] Further, in step S3, 10-100 mg of the carbon-rich carbon nitride conjugated polymer is evenly mixed with 1-10 μl of deionized water to prepare a slurry; the slurry is evenly coated on the TiO2 surface of two conductive glass-TiO2 nanocrystalline mesoporous film composite electrodes by a scraping method.
[0020] The beneficial effects of the present invention are as follows: (1) Material properties. The prior art uses two materials, namely photovoltaic materials and energy storage materials, to generate and store photogenerated charges. The present invention uses one material, namely a carbon-rich carbon nitride conjugated polymer with the dual functions of light absorption and charge storage to achieve photogenerated charge generation and storage. Its advantages are: it greatly simplifies the device structure, avoids the matching and synergistic problems between the two materials, achieves a high level of synergy, effectively reduces internal electron loss and electron transmission loss between electrodes, and improves the photogenerated charge storage capacity. (2) Device structure. No electrolyte is used, which completely avoids a series of problems caused by the electrolyte. For example, unstable performance caused by the volatilization and leakage of the electrolyte; unsafe use caused by the flammability of the electrolyte, etc. All-solid-state devices are more conducive to long-term stability and safety of use, and their integration with other functional devices is also greatly improved. (3) Photogenerated charge storage performance. A single cell can obtain a power of not less than 170mC cm -2 The photogenerated charge storage capacity is -2.5V to 2.5V; the operating voltage window is -2.5V to 2.5V; during the photocharging and discharging process, a significant color change effect occurs, which has visual energy storage characteristics.
[0021] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:
[0023] Figure 1 Schematic diagram of the structure of the optical supercapacitor;
[0024] Figure 2 Process flow chart for preparing optical supercapacitors;
[0025] Figure 3 Typical cyclic voltammetry (CV) curves of all-solid-state optical supercapacitors and their color changes at different potentials;
[0026] Figure 4 The typical charge and discharge curve of the all-solid-state optical supercapacitor;
[0027] Figure 5 This is a diagram showing the energy band structure relationship between titanium dioxide (TiO2) and carbon-rich carbon nitride conjugated polymer (CPCN) in all-solid-state optical supercapacitors; DETAILED DESCRIPTION
[0028] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.
[0029] It should be noted that the illustrations provided in the following embodiments are only schematic illustrations of the basic concept of the present invention, and thus the drawings only show components related to the present invention rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.
[0030] In the following description, numerous details are discussed to provide a more thorough explanation of the embodiments of the present invention. However, it is obvious to those skilled in the art that the embodiments of the present invention can be implemented without these specific details. In other embodiments, well-known structures and devices are shown in the form of block diagrams rather than in detail to avoid making the embodiments of the present invention difficult to understand.
[0031] like Figure 1 As shown, the present invention provides an all-solid-state optical supercapacitor based on carbon-rich carbon nitride conjugated polymer, using conductive glass (FTO or ITO) as a conductive substrate and optical window; using titanium dioxide nanocrystalline mesoporous film as an electron transport material and charge storage auxiliary material; using carbon-rich carbon nitride conjugated polymer (CPCN) as a light absorption and photogenerated charge storage material; and using insulating sealant as an insulating spacer between two conductive band glasses. Thus, a symmetrical capacitor structure without electrolyte is used: conductive glass / / TiO2 / / CPCN / / TiO2 / / conductive glass, to prepare an all-solid-state photogenerated charge storage device.
[0032] like Figure 2 As shown, the process flow of preparing optical supercapacitor is as follows:
[0033] ① Preparation of carbon-rich carbon nitride conjugated polymers.
[0034] ② Sintering a titanium dioxide (TiO2) nanocrystalline mesoporous film of a certain thickness on the conductive glass to obtain a conductive glass / TiO2 nanocrystalline mesoporous film composite electrode.
[0035] ③ Evenly coat the TiO2 surfaces of the two composite electrodes with carbon-rich carbon nitride conjugated polymer (CPCN) for later use.
[0036] ④ Use insulating sealant to bond two composite electrodes loaded with CPCN together to obtain an all-solid-state optical supercapacitor with the structure of "conductive glass / / TiO2 / / CPCN / / TiO2 / / conductive glass".
[0037] like Figure 3 As shown in the figure, when the cyclic voltammetry characteristic test is carried out under illumination, the typical CV curve characteristics of the invented all-solid-state optical supercapacitor are: there are two significant positive current peaks in the range of -0.6V to 0.6V, a low positive current peak in the range of 0.6V to 2.5V; there is a negative current peak in the range of 0.6V to 0V; there are two negative current peaks in the range of 0V to -1.2V. The operating voltage window is -2.5V to 2.5V. As the voltage changes, the device will show a reversible color change from blue → golden yellow → blue.
[0038] like Figure 4 As shown in the figure, when the constant current charge and discharge (GCD) test is carried out under illumination, the typical GCD curve characteristics of the invented all-solid-state optical supercapacitor are as follows: ① The charging voltage range is -0.6V to 2.5V, and the discharge voltage range is 0.6V to -2.5V. ② When charging, there are two linear segments on the GCD curve where the voltage changes with the amount of stored charge; when discharging, there is a linear segment on the GCD curve where the voltage changes with the amount of discharged charge. ③ The coulomb efficiency is greater than 100%.
[0039] like Figure 5 As shown, the energy band structure relationship between titanium dioxide and carbon-rich carbon nitride conjugated polymer used in the present invention is: the band gap value of titanium dioxide is 3.22eV, and the band gap value of carbon-rich carbon nitride conjugated polymer is 1.74eV; the conduction band bottom energy value of titanium dioxide is higher than the LUMO orbital energy value of carbon-rich carbon nitride conjugated polymer; the valence band top energy value of titanium dioxide is higher than the HOMO orbital energy value of carbon-rich carbon nitride conjugated polymer.
[0040] Example 1
[0041] A fully solid-state optical supercapacitor based on a carbon-rich carbon nitride conjugated polymer, the manufacturing process of which comprises the following steps:
[0042] (1) Preparation of carbon nitride-rich conjugated polymers
[0043] Dicyandiamide, citric acid and deionized water are mixed in a mass ratio of 1:1.9:60 to obtain a reactant. The reactant is introduced into a hydrothermal reactor and kept at 200°C for 3 hours for a hydrothermal reaction to obtain a precursor. The precursor is sealed and stored in an ammonia atmosphere at room temperature for 8 months for a aging reaction to obtain an aqueous solution of a carbon-rich carbon nitride conjugated polymer. The aqueous solution of the carbon-rich carbon nitride conjugated polymer is freeze-dried at -80°C and a vacuum degree below 30Pa to obtain a carbon-rich carbon nitride conjugated polymer solid material.
[0044] (2) Preparation of conductive glass / TiO2 nanocrystalline mesoporous film composite electrodes
[0045] Clean the two FTO conductive glasses and set them aside. Sinter the titanium dioxide nanocrystals on the two FTO conductive glasses to obtain two conductive glass / TiO2 nanocrystal mesoporous film composite electrodes with the same area and thickness. The area of the titanium dioxide nanocrystal film is 3 cm × 3 cm and the thickness is 20 μm.
[0046] (3) Assembly of all-solid-state optical supercapacitors based on carbon nitride-rich conjugated polymers
[0047] 10 mg of carbon-rich carbon nitride conjugated polymer was mixed evenly with a small amount of deionized water (about 1 μl) to prepare a thick slurry. The slurry was evenly coated on the TiO2 surface of two conductive glass / TiO2 nanocrystalline mesoporous film composite electrodes by scraping. Then, an appropriate amount of sealing insulating glue was applied to the edges of the two electrodes coated with carbon-rich carbon nitride conjugated polymer, and then they were pressed relatively tightly. After the insulating glue solidified, an all-solid-state optical supercapacitor based on carbon-rich carbon nitride conjugated polymer was obtained.
[0048] The all-solid-state optical supercapacitor based on carbon-rich carbon nitride conjugated polymer fabricated by the above steps can obtain 167mC cm under AM1.5 simulated solar light. -2 of photogenerated charge storage capacity.
[0049] Example 2
[0050] A fully solid-state optical supercapacitor based on a carbon-rich carbon nitride conjugated polymer, the manufacturing process of which comprises the following steps:
[0051] (1) Preparation of carbon nitride-rich conjugated polymers
[0052] Dicyandiamide, citric acid and deionized water are mixed in a mass ratio of 1:1.9:60 to obtain a reactant. The reactant is introduced into a hydrothermal reactor and kept at 200°C for 3 hours for a hydrothermal reaction to obtain a precursor. The precursor is sealed and stored in an ammonia atmosphere at room temperature for 3 months for a aging reaction to obtain an aqueous solution of a carbon-rich carbon nitride conjugated polymer. The aqueous solution of the carbon-rich carbon nitride conjugated polymer is freeze-dried at -80°C and a vacuum degree below 30Pa to obtain a carbon-rich carbon nitride conjugated polymer solid material.
[0053] (2) Preparation of conductive glass / TiO2 nanocrystalline mesoporous film composite electrodes
[0054] Clean the two FTO conductive glasses and set them aside. Sinter the titanium dioxide nanocrystals on the two FTO conductive glasses to obtain two conductive glass / TiO2 nanocrystal mesoporous film composite electrodes with the same area and thickness. The area of the titanium dioxide nanocrystal film is 6 cm×6 cm and the thickness is 30 μm.
[0055] (3) Assembly of all-solid-state optical supercapacitors based on carbon nitride-rich conjugated polymers
[0056] 50 mg of carbon-rich carbon nitride conjugated polymer was mixed evenly with a small amount of deionized water (about 5 μl) to prepare a thick slurry. The slurry was evenly coated on the TiO2 surface of two conductive glass / TiO2 nanocrystalline mesoporous film composite electrodes by scraping. Then, an appropriate amount of sealing insulating glue was applied to the edges of the two electrodes coated with carbon-rich carbon nitride conjugated polymer, and then they were pressed relatively tightly. After the insulating glue solidified, an all-solid-state optical supercapacitor based on carbon-rich carbon nitride conjugated polymer was obtained.
[0057] The all-solid-state optical supercapacitor based on carbon-rich carbon nitride conjugated polymer fabricated by the above steps can obtain 174mC cm under AM1.5 simulated sunlight irradiation. -2 of photogenerated charge storage capacity.
[0058] Example 3
[0059] A fully solid-state optical supercapacitor based on a carbon-rich carbon nitride conjugated polymer, the manufacturing process of which comprises the following steps:
[0060] (1) Preparation of carbon nitride-rich conjugated polymers
[0061] Dicyandiamide, citric acid and deionized water are mixed in a mass ratio of 1:1.9:60 to obtain a reactant. The reactant is introduced into a hydrothermal reactor and kept at 200°C for 3 hours for a hydrothermal reaction to obtain a precursor. The precursor is sealed and stored in an ammonia atmosphere at room temperature for 14 months for a aging reaction to obtain an aqueous solution of a carbon-rich carbon nitride conjugated polymer. The aqueous solution of the carbon-rich carbon nitride conjugated polymer is freeze-dried at -80°C and a vacuum degree below 30Pa to obtain a carbon-rich carbon nitride conjugated polymer solid material.
[0062] (2) Preparation of conductive glass / TiO2 nanocrystalline mesoporous film composite electrodes
[0063] Clean the two FTO conductive glasses and set them aside. Sinter the titanium dioxide nanocrystals on the two FTO conductive glasses to obtain two conductive glass / TiO2 nanocrystal mesoporous film composite electrodes with the same area and thickness. The area of the titanium dioxide nanocrystal film is 9 cm×9 cm and the thickness is 10 μm.
[0064] (3) Assembly of all-solid-state optical supercapacitors based on carbon nitride-rich conjugated polymers
[0065] 100 mg of carbon-rich carbon nitride conjugated polymer was mixed evenly with a small amount of deionized water (about 10 μl) to prepare a thick slurry. The slurry was evenly coated on the TiO2 surface of two conductive glass / TiO2 nanocrystalline mesoporous film composite electrodes by scraping. Then, an appropriate amount of sealing insulating glue was applied to the edges of the two electrodes coated with carbon-rich carbon nitride conjugated polymer, and then they were pressed relatively tightly. After the insulating glue solidified, an all-solid-state optical supercapacitor based on carbon-rich carbon nitride conjugated polymer was obtained.
[0066] The all-solid-state optical supercapacitor based on carbon-rich carbon nitride conjugated polymer fabricated by the above steps can obtain 177mC cm under AM1.5 simulated sunlight irradiation. -2 of photogenerated charge storage capacity.
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.
Claims
1. An all-solid-state optical supercapacitor based on carbon-nitride-rich conjugated polymer, characterized in that: It includes a first conductive glass and a second conductive glass; the conductive surface of the first conductive glass is provided with a first titanium dioxide nanocrystalline mesoporous film; the conductive surface of the second conductive glass is provided with a second titanium dioxide nanocrystalline mesoporous film; a carbon-rich carbon nitride conjugated polymer is provided between the first titanium dioxide nanocrystalline mesoporous film and the second titanium dioxide nanocrystalline mesoporous film; the first titanium dioxide nanocrystalline mesoporous film, the second titanium dioxide nanocrystalline mesoporous film and the outer sides of the carbon-rich carbon nitride conjugated polymer are sealed by an insulating sealant.
2. A method for preparing an all-solid-state optical supercapacitor based on a carbon-rich carbon nitride conjugated polymer, characterized in that: The following steps are involved: S1: Preparation of carbon nitride-rich conjugated polymers; S2: Sintering titanium dioxide nanocrystalline mesoporous thin films on the conductive surfaces of two pieces of conductive glass to obtain a conductive glass-TiO2 nanocrystalline mesoporous thin film composite electrode; S3: Uniformly coating the carbon nitride-rich conjugated polymer on the surface of the titanium dioxide nanocrystalline mesoporous film of the two composite electrodes; S4: Two composite electrodes coated with carbon-rich carbon nitride conjugated polymers are bonded together using an insulating sealant to obtain an all-solid-state optical supercapacitor.
3. The method for preparing an all-solid-state optical supercapacitor based on a carbon-rich carbon nitride conjugated polymer according to claim 2, characterized in that: The preparation steps of the carbon-rich carbon nitride conjugated polymer are as follows: S11: dicyandiamide, citric acid, and deionized water are mixed in a mass ratio of 1:1.9:60 to obtain a reactant; S12: introducing the reactants into a hydrothermal reactor and keeping the temperature at 200° C. for 3 hours to perform a hydrothermal reaction to obtain a precursor; S13: sealing and storing the precursor at room temperature in an ammonia atmosphere for 3 to 14 months for aging reaction to obtain an aqueous solution of a carbon nitride-rich carbon conjugated polymer; S14: freeze-drying the aqueous solution of the carbon-rich carbon nitride conjugated polymer at -80°C and a vacuum degree below 30 Pa to obtain a carbon-rich carbon nitride conjugated polymer solid material.
4. The method for preparing an all-solid-state optical supercapacitor based on a carbon-rich carbon nitride conjugated polymer according to claim 2, characterized in that: The titanium dioxide nanocrystalline film has an area of 3cm×3cm to 9cm×9cm and a thickness of 10 to 30 μm.
5. The method for preparing an all-solid-state optical supercapacitor based on a carbon-rich carbon nitride conjugated polymer according to claim 2, characterized in that: In step S3, 10-100 mg of carbon-rich carbon nitride conjugated polymer is evenly mixed with 1-10 μl of deionized water to prepare a slurry; the slurry is evenly coated on the TiO2 surface of two conductive glass-TiO2 nanocrystalline mesoporous film composite electrodes by a scraping method.
Citation Information
Patent Citations
All-solid-state supercapacitor with photoelectric conversion function and preparation method thereof
CN113571341A
Photochargeable homojunction electrode based on water-soluble carbon-rich carbon nitride polymer and preparation method and application thereof
CN115621053A
Polymer-carbon nitride composite powder material and preparation method thereof
CN117101722A
Electro-photochromic device based on carbon-rich carbon nitride conjugated polymer and assembling method and application thereof
CN117555185A
Electrochemical energy storage devices
US20230118610A1